In situ synthesis and improved photoelectric performances of a Sb2Se3/β-In2Se3 heterojunction composite with potential photocatalytic activity for methyl orange degradation. Issue 16 (November 2020) - Ren, Donglou; Merdrignac-Conanec, Odile; Dorcet, Vincent; Cathelinaud, Michel; Zheng, Zhuanghao; Ma, Hongli; Zhang, Xianghua
Abstract: A series of Sb2 Se3 /β-In2 Se3 heterojunction composites with different contents of β-In2 Se3 were successfully synthesized via an in-situ melt-quenching method. The relationship between structure and photoelectric performances was systematically investigated by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, energy-dispersive spectrometry, UV–Vis optical absorption, and photoelectrochemical measurement. The direct band energy of the composites was in the range of 1.15–1.18 eV, implying strong visible light harvesting ability. Meanwhile, the number of heterojunctions and the connectivity of β-In2 Se3 crystals could be adjusted by changing the content of β-In2 Se3 . As a result, the optimized composites (Sb2 Se3 -10% β-In2 Se3 ) exhibited remarkable photocurrent density that was about 283 times higher than that of pure Sb2 Se3 . Moreover, the response and recovery times were faster than that of previous reported Sb2 Se3 . The interface charge separation and transport mechanism for the improved photoelectric performances was proposed based on the experimental results. Thanks to the remarkable photocurrent density, a potential application was also evaluated by photocatalytic degradation of MO (Methyl Orange) solution. After 180 min of illumination, 76% of MO dye could been decomposed. This work will provide the direct guidance for constructing Sb2 Se3 /β-In2 Se3 heterojunction devices for harvesting solar energy.